Leishmania infection and host-blood feeding preferences of phlebotomine sandflies and canine leishmaniasis in an endemic European area, the Algarve Region in Portugal - Maia, Carla (2018)
The Algarve Region (AR) in southern Portugal, which is an international tourist destination, has been considered an endemic region of zoonotic leishmaniasis caused by Leishmania infantum since the 1980s. In the present study, phlebotomine and canine surveys were conducted to identify sandfly blood meal sources and to update the occurrence of Leishmania infection in vectors and dogs. Four sandfly species were captured: Phlebotomus perniciosus, Phlebotomus ariasi, Phlebotomus sergenti and Sergentomyia minuta. In one P. perniciosus female, L. infantum DNA was detected. Blood meal tests showed that this species had no host preferences and was an opportunistic feeder. An overall canine leishmaniasis (CanL) seroprevalence of 16.06% was found; the seroprevalence was 3.88% in dogs housed in kennels and 40.63% in dogs that attended veterinary clinics. The simultaneous occurrence of dogs and P. perniciosus infected with L. infantum in the AR indicates that the region continues to be an endemic area for CanL. Our results reinforce the need for the systematic spatial distribution of phlebotomine populations and their Leishmania infection rates and the need to simultaneously perform pathogen monitoring in both invertebrate and vertebrate hosts to investigate the transmission, distribution and spreading of Leishmania infection.